2018
DOI: 10.1186/s12889-018-5872-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cigarette smoking and smoking intensity among adult males in Ghana

Abstract: BackgroundIn spite of the adverse health and financial implications of smoking, it still remains one of the leading causes of preventable diseases and deaths in the world. Key to discouraging the habit of smoking is knowledge of the drivers of smoking. In Ghana, though smoking behaviours are relatively more associated with adult males than youth and adolescents, studies on smoking behaviours of adult males are scant. This study, therefore, investigates the determinants of cigarette smoking and smoking intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 31 publications
(25 reference statements)
17
43
1
Order By: Relevance
“…For instance, young men with poorer, middle, richer and richest wealth status had a lesser likelihood of using tobacco compared to those from the poorest wealth status. This finding is consistent with the studies of Shrestha et al [6], Nketiah -Ampoosah, Afful -Mensah and Ampaw [10] and Abdulrahim and Jawad [23]. Our study found a significant association between the type of occupation and tobacco use.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…For instance, young men with poorer, middle, richer and richest wealth status had a lesser likelihood of using tobacco compared to those from the poorest wealth status. This finding is consistent with the studies of Shrestha et al [6], Nketiah -Ampoosah, Afful -Mensah and Ampaw [10] and Abdulrahim and Jawad [23]. Our study found a significant association between the type of occupation and tobacco use.…”
Section: Discussionsupporting
confidence: 94%
“…Young men with a primary, secondary and higher level of education had lesser odds of consuming tobacco as compared with those with no education. This finding is in line with earlier studies [6,10,14,22]. The possible explanation would be the educated young men may be exposed to information about the dangerous health risks associated with the consumption of tobacco and are more likely to stay away from consuming tobacco in any form.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This nding contradicts earlier comprehensive review of smoking prevalence in Ghana, which reported high incidence in older men [42]. We agree with the reasoning put forth by Nketiah and colleagues [43] that factors such as religion, level of income, educational status, and public health could account for the low prevalence in the study population. Furthermore, we showed no association of smoking and prostate cancer (OR, 1.007; Cl 95%).…”
Section: Resultscontrasting
confidence: 73%
“…Parental education is, as such, very important. Women tend to smoke less because of personality traits [82] as well as, especially in countries like Iran, for cultural reasons and stigma. Unfortunately, adolescent boys, due to the high influence of their friends, see smoking as a sign of adulthood, and their lack of awareness and education has made them more likely to smoke than adolescent girls [74,80,81].…”
Section: Discussionmentioning
confidence: 99%